Prognostic Potential of Liver Enzymes in Patients With COVID-19 at the Leishenshan Hospital in Wuhan - Liu, Zeming; Hu, Di; Li, Jinpeng; Xia, Qing; Gong, Yan; Li, Zhengwei; Wu, Qian; Yi, Meilin; Huang, Yihui; Wu, Meng; Guo, Liang; Wu, Xiaohui (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Coronavirus disease 2019 (COVID-19) has evolved into a pandemic. We hypothesized that biochemical indicators of liver function may help determine the prognosis of COVID-19 patients. Methods: Patient information was collected from the Wuhan-Leishenshan hospital. Logistic and Cox regression analyses, Kaplan-Meier curves, and Curve fitting were used to determine the correlation between elevated levels of aspartate transaminase (AST), alanine transaminase (ALT), and AST/ALT and severity of disease/mortality. Results: Logistic and Cox regression analyses and Kaplan-Meier survival curves showed that COVID-19 progression correlated with elevated levels of AST and AST/ALT. The odds ratios for elevated levels of AST and AST/ALT in patients were 0.818 (95% confidence interval [CI]: 0.274-2.441, P = 0.035) and 2.055 (95% CI: 1.269-3.327, P = 0.003), respectively; the hazard ratios were 4.195 (95% CI: 1.219-14.422, P = 0.023) and 3.348 (95% CI: 1.57-7.139, P = 0.002), respectively. The Kaplan-Meier survival curves demonstrated that patients with elevated AST and AST/ALT levels had a higher risk of developing severe COVID-19. Conclusion: Elevated AST and AST/ALT levels correlated with severity of COVID-19 and mortality. Liver function tests may help clinicians in determining the prognosis of patients undergoing treatment for COVID-19.